2008
DOI: 10.1007/s10729-008-9085-4
|View full text |Cite
|
Sign up to set email alerts
|

The timing of adoption of positron emission tomography: a real options approach

Abstract: This paper presents the economic evaluation from a hospital's perspective of the investment in positron emission tomography, adopting a real options approach. The installation of this equipment requires a major capital outlay, while uncertainty on several key variables is substantial. The value of several timing strategies, including sequential investment, is determined taking into account that future decisions will be based on the information available at that time. The results show that adopting this approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Another related approach is the real options approach, which has been applied in various applications, investment decisions regarding imaging techniques [23], and medical decision making in risky surgery [24]. Usually, however, an analytical solution can be obtained only by imposing strict assumptions on the distributions of the parameters involved that will not be met in practice.…”
Section: Discussionmentioning
confidence: 99%
“…Another related approach is the real options approach, which has been applied in various applications, investment decisions regarding imaging techniques [23], and medical decision making in risky surgery [24]. Usually, however, an analytical solution can be obtained only by imposing strict assumptions on the distributions of the parameters involved that will not be met in practice.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, "access with evidence development" schemes are not an option, and ROA provides evidence-based arguments that can be used for decision making. A real options approach has also been used in a recent study to examine whether hospitals should invest in positron emission tomography [44,45]. From the present study we found that adopting proton therapy and including all patients in the trial, which resembles the scheme, was never preferred, even when there were no reversal costs.…”
Section: Discussionmentioning
confidence: 77%
“…In 2008, the studies continue to focus mainly on investment analysis and, as shown by Levaggi and Moretto (2008), Pertile (2008), Pertile, Torri, Flor and Tardivo (2008) and Eckermann and Willan (2008). The first study evaluated a relationship between quality and investment in health technology.…”
Section: Real Options Theory In Healthmentioning
confidence: 99%
“…In addition, it was analyzed the role of alternative payment systems. In the next study, Pertile, Torri, Flor and Tardivo (2008) In 2009, the studies were developed had several focuses. It was observed studies to evaluate investment, such as Özogul, Karsak, and Tolga (2009), which valued an Enterprise Resource Planning -ERP system investment incorporating multiple options.…”
Section: Real Options Theory In Healthmentioning
confidence: 99%